Sensitivity Analysis of the Agricultural Policy/Environmental eXtender (APEX) for Phosphorus Loads in Tile‐Drained Landscapes. Issue 4 (1st July 2015) - Ford, W.; King, K.; Williams, M.; Williams, J.; Fausey, N.
Abstract : Numerical modeling is an economical and feasible approach for quantifying the effects of best management practices on dissolved reactive phosphorus (DRP) loadings from agricultural fields. However, tools that simulate both surface and subsurface DRP pathways are limited and have not been robustly evaluated in tile‐drained landscapes. The objectives of this study were to test the ability of the Agricultural Policy/Environmental eXtender (APEX), a widely used field‐scale model, to simulate surface and tile P loadings over management, hydrologic, biologic, tile, and soil gradients and to better understand the behavior of P delivery at the edge‐of‐field in tile‐drained midwestern landscapes. To do this, a global, variance‐based sensitivity analysis was performed, and model outputs were compared with measured P loads obtained from 14 surface and subsurface edge‐of‐field sites across central and northwestern Ohio. Results of the sensitivity analysis showed that response variables for DRP were highly sensitive to coupled interactions between presumed important parameters, suggesting nonlinearity of DRP delivery at the edge‐of‐field. Comparison of model results to edge‐of‐field data showcased the ability of APEX to simulate surface and subsurface runoff and the associated DRP loading at monthly to annual timescales; however, some high DRP concentrations and fluxes were not reflected in the model, suggesting the presence of preferential flow. Results from this study provide new insights into baseline tile DRP loadings that exceed thresholds for algal proliferation. Further, negative feedbacks between surface and subsurface DRP delivery suggest caution is needed when implementing DRP‐based best management practices designed for a specific flow pathway.